Survival of oral tongue squamous cell carcinoma in young adults. Issue 9 (15th April 2019) - Oliver, Jamie R.; Wu, S. Peter; Chang, Clifford M.; Roden, Dylan F.; Wang, Binhuan; Hu, Kenneth S.; Schreiber, David; Givi, Babak
Abstract: Background: Small cohort studies have suggested oral tongue squamous cell carcinoma (OTSCC) could be associated with worse prognosis in individuals younger than 40. Methods: We compared the survival of all OTSCC cases in the National Cancer Database under 40 years old with those older than 40, excluding patients over 70. Cox regression and propensity score matched (PSM) survival analyses were performed. Results: A total of 22 930 OTSCC patients were identified. The under 40 group consisted of 2566 (9.9%) cases; 20664 were 40 to 70 (90.1%). Most were male (13 713, 59.8%), stage I‐II (12 754, 72.4%), and treated by surgery alone (13 973, 63.2%). Survival in patients under 40 was higher (79.6% vs 69.5%, P < .001). In PSM analysis (n = 2928) controlling for all 10 significant factors in multivariate regression, patients under 40 had a 9% higher 5‐year survival (77.1% vs 68.2%, P < .001). Conclusion: Contrary to the prior reports, younger patients with OTSCC did not have worse survival in the National Cancer Database.